PENGARUH FEE AUDIT, KOMPETENSI AUDITOR, ETIKA AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT KANTOR AKUNTAN PUBLIK WILAYAH BALI - Ni Made Sunarsih; Ni Putu Shinta Dewi; I Made Candra Wira Wiguna (Jurnal Widya Akuntansi dan Keuangan, 2019)
Audit quality is very important in order to maintain the trust of clients and those who use audit reports. The profession of public accounting is a profession of public trust. From the profession of public accounting, the public expects a free and impartial assessment of the information presented by company management in financial statements where the public accounting profession is responsible for raising the level of reliability of the company's financial statements, so that people obtain reliable financial information as a basis for decision making. This study aims to re-examine the effect of audit fee variables, auditor competence, auditor ethics and time budget pressure on audit quality. The type of data used is primary data. This research was conducted at the Bali Regional Public Accountant Office. The sampling technique uses purposive sampling technique. The data analysis technique uses multiple linear regression. The population in this study were 86 auditor samples in this study were 39 auditors who worked at least 1 year and had been assigned to field work. Based on the results of the study showed that the audit fee variable, auditor competency and auditor ethics had a positive effect on audit quality at the Bali Regional Public Accountant Office. While the results of the study show that the time budget pressure variables negatively affect audit quality at the Bali Regional Public Accountant Office.